STRUCTURE AND ROBUST OPTIMIZATION DESIGN BASED ON ADDITIONAL OBJECTIVE FUNCTION OF THE SENSITIVITY - HAO FangFang; FAN XiaoNing; ZHI Bo (Jixie qiangdu)
A robust-optimization-design method based on sensitivity’s analysis of the crane metal structure is described. It considers uncertain factors existing in the design of crane metal structure. And the multi-objective robust-optimization design model about crane metal structure is constructed on the bases of the sensitivity and the grey correlation theory. Taking the bridge crane girder as the research object and getting the best solution of the multi-objective optimization problems by grey-absolutecorrelation degree and the MATLAB optimization-design toolbox on the basis of the sensitivity analysis for its each performance.The results shows that when considers the uncertain factors of structure,the model about robust optimization design constructed in this paper and the grey correlation degree of multi-objective optimization method can ensure the steady and safety,and also can lose weight of the crane girder structure. The paper provides the technical guidance for the robust optimization of the other complex structure.